Error Control in Wireless Sensor Networks: A Cross Layer Analysis - Vuran, M.C.; Akyildiz, I.F. (IEEE/ACM transactions on networking, 2009)
Error control is of significant importance for wireless sensor networks (WSNs) because of their severe energy constraints and the low power communication requirements. In this paper, a cross-layer methodology for the analysis of error control schemes in WSNs is presented such that the effects of multi-hop routing and the broadcast nature of the wireless channel are investigated. More specifically, the cross-layer effects of routing, medium access, and physical layers are considered. This analysis enables a comprehensive comparison of forward error correction (FEC) codes, automatic repeat request (ARQ), and hybrid ARQ schemes in WSNs. The validation results show that the developed framework closely follows simulation results.